World Bank Corporate Scorecard 2011 : Integrated Results and Performance Framework - World Bank (Washington, DC, 2013)
The Corporate Scorecard is designed to provide a snapshot of the Bank’s overall performance, including its business modernization, in the context of development results. It facilitates strategic dialogue between Management and the Board on progress made and areas that need attention. The World Bank has comprehensive systems— on which it continuously improves—for measuring and monitoring both development results and its own performance. These systems are complemented by independent evaluation. With the Results Measurement System, which was adopted for the 13th replenishment of the International Development Association (IDA13) in 2002, the Bank became the first multilateral development institution to use a framework with quantitative indicators to monitor results and performance. The Corporate Scorecard expands this approach to the entire World Bank covering both the International Bank for Reconstruction and Development (IBRD) and IDA.